(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Convulsion is one of the most common neurological conditions that occur in children. Electrolyte imbalance is one underlying cause that, if managed appropriately, can prevent further recurrences of seizures. Hence, this study aims to assess the electrolyte imbalances that may be found in convulsive patients at a Pediatric Intensive Care (PICU) setting of a tertiary care hospital. Materials and methods: It was a cross-sectional observational study carried out in the Department of Pediatrics of Chattagram Maa - Shishu O General Hospital. The study period was six months from January 2019 to July 2019. 100 study subjects aged one month to fifteen years admitted to the Pediatric ICU with convulsions were enrolled as study subjects. After stabilization of convulsions, detailed history and clinical examination were recorded. Along with other routine investigations, S. Electrolytes, S. Calcium and S. Magnesium were investigated and analyzed. Results: The age range was 2 months to 8 years. Male participants were more than female, 73(73%) vs. 27(27%). Electrolyte imbalance was found in more than half 56(56%) of the children admitted. Among them hypocalcaemia was the most common finding 33(33%), followed by hypomagnesaemia 17(17%), hypokalemia 9(9%) and finally hyponatremia 7(7%). A significant number of patients with hyponatremia (p <0.001) and hypocalcemia (p<0.049) showed poor GCS score when it was compared with electrolyte imbalance. Encephalitis and complex febrile seizure were the common causes of convulsion in this study, 36(36%) and 32(32%) respectively. Meningitis, status epilepticus, cerebral palsy with seizure disorder and other causes were found in 13(13%) 10(10%), 3(3%) and 6(6%) cases, respectively. Electrolyte imbalances were mostly observed in cases with encephalitis 36(36%) complex febrile seizure 32(32%) and meningitis 13(13%). There are significant differences in calcium levels in cases with complex febrile seizure (p=0.02) and status epilepticus (p=0.006). Conclusion: Electrolyte imbalances are common in children with convulsions. It occurs either as a consequence of an underlying cause of convulsion (eg, Febrile seizure) or can itself be the cause for convulsion in some cases. If these imbalances are corrected recurrence of convulsion as well as use of antiepileptic drugs can be limited. Chatt Maa Shi Hosp Med Coll J; Vol.25 (1); January 2026; Page 73-78